IMPLEMENTASI ALGORITMA K-NEAREST NEIGHBOR (KNN) UNTUK KLASIFIKASI PELAYANAN PUBLIK - Sitorus, Betharia Novalina; Harmayani, Harmayani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Public service is any form of service provided by the government, whether organized by the government institution itself or by non-government institutions to meet the needs of the community or the implementation of provisions that have been determined with all means and equipment through certain work procedures in order to provide services in the form of goods and services. Public service referred to in this study includes all forms of service to the community carried out by the District in meeting the needs of the community which are carried out based on the principles, principles and standards of public service in order to realize a democratic government. The purpose of the study is to apply the KNN method to the system to be designed. The data inputted into this system is public service work data. The testing process produces new information that when the researcher inputs a work time value of 45 minutes, a constraint value of 2, a completion status value of 3 and a test of K = 3, K = 5, K = 7 the classification is good with a distance of K = 3 (0.006666666667). The designed application can solve the problem of classifying public services based on the achievements of the public service division so that leaders can see which work needs to be evaluated because of the long process. Keywords: Implementation, K-Nearest Neighbor (KNN) Algorithm, Public Service Classification, Web Abstrak: Pelayanan publik merupakan segala bentuk pelayanan yang diberikan oleh pemerintah baik yang diselenggarakan oleh lembaga pemerintah itu sendiri ataupun oleh lembaga non-pemerintah untuk memenuhi kebutuhan masyarakat maupun pelaksanaan ketentuan yang telah ditetapkan dengan segala sarana, dan perlengkapannya melalui prosedur kerja tertentu guna memberikan jasa pelayanan dalam bentuk barang dan jasa. Pelayanan publik yang dimaksud dalam penelitian ini termasuk dalam segala bentuk pelayanan pada masyarakat yang dilakukan oleh Kecamatan dalam memenuhi kebutuhan masyarakat yang dilakukan berdasarkan asas, prinsip dan standar pelayanan publik agar mewujudkan pemerintahan yang demokratis. Tujuan penelitian untuk menerapkan metode KNN pada sistem yang akan dirancang. Data yang diinputkan dalam sistem ini ialah data pengerjaan pelayanan publik. Proses pengujian menghasilkan informasi baru bahwa ketika peneliti menginputkan nilai waktu pengerjaan 45 menit, nilai kendala 2, nilai status penyelesaian 3 dan ujia K = 3, K = 5, K = 7 klasifikasinya adalah bagus dengan jarak K = 3 (0.0066666666667). Aplikasi yang dirancang dapat menyelesaikan permasalahan mengklasifikasikan pelayanan publik berdasarkan pencapaian kerja bagian pelayanan publik sehingga pemimpin dapat melihat pekerjaan yang perlu dievaluasi berdasarkan waktu pengerjaannya. Kata kunci: Implementasi, Algoritma K-Nearest Neighbor (KNN), Klasifikasi Pelayanan Publik, Web.